Determination of 6258-70, a new semi-synthetic taxane, in rat plasma and tissues: Application to the pharmacokinetics and tissue distribution study - Simin Zhao; Yuanyuan Zhang; Ping Ju; Liqiang Gu; Rui Zhuang; Longshan Zhao; Xing Tang; Kaishun Bi; Xiaohui Chen (Journal of Pharmaceutical Analysis, 2016)
Cancer is the leading cause of death all over the world. Among the chemotherapy drugs, taxanes play an important role in cancer treatment. 6258-70 is a new semi-synthetic taxane which has a broad spectrum of antitumor activity. A fast and reliable high performance liquid chromatography-tandem mass spectrometry (HPLC–MS/MS) method was developed for quantification of 6258-70 in rat plasma and tissues in this paper. After extraction by liquid-liquid extraction method with methyl tert-butyl ether, the samples were separated on a Kinetex C18 column (50 mm×2.1 mm, 2.6 µm, Phenomenex, USA) within 3 min. The method was fully validated with the matrix effect between 87.7% and 99.5% and the recovery ranging from 80.3% to 90.1%. The intra- and inter-day precisions were less than 9.5% and the accuracy ranged from −3.8% to 6.5%. The reliable method was successfully applied to the pharmacokinetics and tissue distribution studies of 6258-70 after intravenous administration in rats. The pharmacokinetic results indicated that the pharmacokinetic behavior of 6258-70 in rats was in accordance with linear features within tested dosage of 1 to 4 mg/kg, and there was no significant difference between the two genders. The tissue distribution study showed that 6258-70 had an effective penetration, spread widely and rapidly and could cross blood-brain barrier. The results of pharmacokinetics and tissue distribution may provide a guide for future study.